What happens after self-harm? An exploration of self-harm and suicide using the Northern Ireland Registry of Self-Harm - Aideen Maguire; Emma Ross; Foteini Tseliou; Denise O'Hagan; Dermot O'Reilly (International Journal of Population Data Science, 2019)
Background Suicide is a major public health concern and Northern Ireland (NI) has the highest rate of both self-harm and suicide in the UK and Ireland. In order to target prevention strategies effectively, it is vital to understand who is most at risk.